The Beautiful and the Damned:Exploring the Negative Side of Masculine Attractiveness in Hiring Situation - Spencer Turner; Sean Willman; Robert Wright (Undergraduate Research Journal for the Human Sciences, 2016)
Although attractiveness can be an asset in many different situations, in some cases, attractiveness can produce negative outcomes in the workplace, which is known as the “beauty is beastly” effect (Heilman & Saruwatari, 1979). This study sought to explore this effect among men in hypothetical hiring decisions using two photos of men that varied in perceived attractiveness. Two-Way ANOVA results showed that the male attractive candidate was rated less favorably among male participant-raters while the average candidate received higher ratings from same-gender participants (F[1, 125] = 8.05, p = .005, η2 = .061). These findings highlight the possibility of male same-gender discrimination based on attractiveness, which is important given that many men will be evaluated by same-gender colleagues throughout their careers.
Keywords: Beautiful; Masculine